Use of Transverse Abdominis block for Post Operative pain management in Patients undergoing Emergency Cesarean Sections : a prospective study - Keerty Garg; Mohit Jindal; Pranav Gupta; Aseem Garg (Медицина болю, 2024)
INTRODUCTION